Fighting Against Corruption: Does Anti-corruption Training Make Any Difference? - Hauser, Christian (Journal of business ethics, 2019)
Corruption continues to represent a tenacious challenge to internationally active companies. According to prevailing international anti-corruption standards, a company can be held criminally liable if it does not put all necessary and reasonable organizational measures in place to prevent corruption. The regular training of employees is considered one of the most effective ways to prevent corruption. Employee training is considered helpful in efforts to minimize the risk of employees becoming involved in corrupt behavior. With this idea in mind and building on the fraud triangle model and neutralization theory, this paper examines whether business professionals who have undergone anti-corruption training are more likely to reject prevailing justifications of corrupt practices than are those who have not undergone such training. The empirical analysis in this paper is based on regression models using data obtained from a unique dataset that includes 200 business professionals. The findings provide evidence that training is positively linked to the likelihood of rejecting justifications of corruption. However, the research also suggests that methods of training must become more specific in order to tackle challenging questions regarding the gray areas of ethics and compliance.